The Reinstatement of Repealed Norms: A Paradox in Post–Constitutional Court Legislative Practice - Adeb Davega Prasna; Adelia Putri; Meri Yarni (Constitutionale, 2025)
The Constitutional Court is authorized to review statutes against the 1945 Constitution of the Republic of Indonesia,, and its decisions are final and binding. However, the absence of an explicit prohibition against reenacting annulled norms in Law Number 12 of 2011 in conjunction with Law Number 13 of 2022 on the Formation of Legislation creates legal uncertainty and risks weakening the authority of the Court. This study analyzes the legal implications of Constitutional Court decisions for lawmakers in regulating a prohibition on reenacting revoked norms within the framework of the rule of law. Using a normative legal method with statutory, conceptual, and case approaches, the study finds that Constitutional Court decisions are erga omnes and obligate lawmakers to follow up through amendment, revocation, or normative adjustment. The absence of explicit regulation enables the recurrence of unconstitutional norms and undermines constitutional supremacy. Therefore, clear statutory provisions prohibiting the reenactment of annulled norms are necessary to strengthen legal certainty and preserve the authority of Constitutional Court decisions.